Seasonal influenza during pregnancy. (March 2021) - Abdullahi, Hala; Elnahas, Amir; Konje, Justin C.
Abstract: Seasonal Influenza is an acute respiratory illness caused by Influenza A or B viruses. Its presentation is commonly with signs and symptoms of upper respiratory tract involvement such as cough, sore throat and runny nose, associated with generalized systemic symptoms such as fever, headaches, myalgia, and weakness. The severity of symptoms is very variable, ranging from mild self-limiting infection to severe acute respiratory illness requiring intensive interventions. It usually occurs during the winter season and can lead to outbreaks and epidemics worldwide. Influenza is associated with increased morbidity and mortality in high-risk populations including pregnant women and up to two weeks postpartum. Rapid and accurate diagnosis of Influenza is necessary for prompt treatment to reduce morbidity. General public health measures and vaccination are recommended to reduce morbidity and control the spread of the disease. There are many published articles on the several Influenza epidemics that have occurred in this century. In this article, we aim to review the epidemiology, clinical manifestations, diagnosis, treatment, and prevention of seasonal Influenza during pregnancy. We performed an electronic search on PubMed, Cochrane database, National guidelines clearing house and Google Scholar databases.